Finnish energy policy trends 1995-2013 : a policy orientation towards the low carbon future? - Heikkinen, Sarita (2014)
Climate change is a very topical issue which requires urgent actions from the international climate change regime and from the nation states inside the regime. At the moment, the global economy is still relying heavily on the traditional energy sources. In order to mitigate the growing pressure of the climate change, a technology modernization which relies on the alternative energy sources is a must. This research examines if the Finnish energy policy trends have been manifesting a policy orientation towards the low carbon future during the time period of 1995-2013 and whether these trends have been in tune with the global climate change regime. The data for this research was collected from the Conventions that Finland has made with the other nation states between the years 1995 to 2013. The selected time period provided 39 findings which were analyzed with the help of the inductive content analysis. The research revealed that the most important Finnish energy policy trends were environmental sustainability and climate change, technology modernization, regional cooperation and reconstruction of governance which all manifested a policy orientation towards the low carbon future, although the transformation process was not very fast by its nature. In addition, the biggest want of the climate change regime i.e. climate change mitigation and biggest need of the regime i.e. de-carbonization of the energy sector, were both very much visible in the results. This suggests that the Finnish energy policies have been mostly in tune with the international regime, albeit the fact that the issue of the decarbonization is far more complex by its nature and more research work related to the area is needed.